2022
DOI: 10.1111/gcb.16217
|View full text |Cite
|
Sign up to set email alerts
|

Impoundment increases methane emissions in Phragmites‐invaded coastal wetlands

Abstract: Saline tidal wetlands are important sites of carbon sequestration and produce negligible methane (CH 4 ) emissions due to regular inundation with sulfate-rich seawater. Yet, widespread management of coastal hydrology has restricted tidal exchange in vast areas of coastal wetlands. These ecosystems often undergo impoundment and freshening, which in turn cause vegetation shifts like invasion by Phragmites, that affect ecosystem carbon balance. Understanding controls and scaling of carbon exchange in these unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 120 publications
2
13
0
Order By: Relevance
“…These results are similar to previous studies in other tropical regions of Australia, which showed that ponded freshwater wetlands emit many more times CH 4 than the natural coastal wetlands they usually replaced (Iram et al 2021). A recent study carried on in North America also displayed that freshening impounded conditions led to a 50‐fold increase in CH 4 emissions compared to saline tidal wetlands (Sanders‐DeMott et al 2022). Furthermore, a meta‐analysis of the impact of converting coastal wetlands into constructed wetlands, cropland, or aquaculture ponds found an increase in the global warming potential associated with land use and cover change by a factor of 7 to 25 (Tan et al 2020).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results are similar to previous studies in other tropical regions of Australia, which showed that ponded freshwater wetlands emit many more times CH 4 than the natural coastal wetlands they usually replaced (Iram et al 2021). A recent study carried on in North America also displayed that freshening impounded conditions led to a 50‐fold increase in CH 4 emissions compared to saline tidal wetlands (Sanders‐DeMott et al 2022). Furthermore, a meta‐analysis of the impact of converting coastal wetlands into constructed wetlands, cropland, or aquaculture ponds found an increase in the global warming potential associated with land use and cover change by a factor of 7 to 25 (Tan et al 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Dark chambers do not account for CO 2 uptake by primary production; therefore, CO 2 measurements reflect only respiration, not their full net balance. We display results as area per hour, as diurnal variation of CH 4 was not captured in this study (Sanders-DeMott et al 2022).…”
Section: Ghg Emissionsmentioning
confidence: 99%
“…Despite the limitations of static chamber‐based measurements compared to eddy‐covariance techniques, chambers provide utility in measuring fluxes from smaller marshes where the flux tower approach is not possible (Baldocchi et al., 1988; Czapla et al., 2020a), such as the fringe marsh we study here and the ecological zones within it. It is not uncommon to scale chamber‐based flux measurements to annual estimates (Anisfeld & Hill, 2012; Weston et al., 2014), with recent work highlighting reasonable agreement between chamber‐based and tower‐based annual measurements (Czapla et al., 2020a; Sanders‐DeMott et al., 2022). Nevertheless, our model results should be treated as first‐order estimates that allow us to compare ER to other components of the C budget at this particular site.…”
Section: Discussionmentioning
confidence: 98%
“…We used the temperature response function of ER calculated above, combined with our high frequency sediment and air temperature data collected every 5 min over the duration of this study to estimate annual ER fluxes across both marsh zones. Scaling chamber‐based flux measurements to annual estimates is not uncommon (Anisfeld & Hill, 2012; Weston et al., 2014), with tenable agreement observed recently between chamber‐based and tower‐based annual measurements (Czapla et al., 2020a; Sanders‐DeMott et al., 2022). While instantaneous ER was better described by air temperatures, we modeled fluxes based on both air and sediment temperatures (Figure S2 of Supporting Information ), as ER includes respiration from both above and belowground processes.…”
Section: Methodsmentioning
confidence: 93%
“…Wang and Cai (2004) first estimated the CO 2 efflux of an inundated marsh (including the tidal creek and flooded platform) using an approach that was coarse in spatiotemporal scales, where only high tide and low tide samples were collected in tidal creeks. In the preponderance of studies, respired CO 2 loss has been estimated using eddy covariance towers (e.g., Baldocchi 2014; Sanders‐DeMott et al 2022; Shahan et al 2022) and static chamber methods (e.g., Kuehn et al 2004; Moseman‐Valtierra et al 2016). These methods may have difficulty to specifically resolve vertical CO 2 fluxes via air–water exchange from other vertical CO 2 fluxes due to the relatively short duration and periodicities of tidal flooding on marsh platforms.…”
mentioning
confidence: 99%